Growth, Impact, and Projection: A New Stage for Science from the Orinoquía (Boletín Semillero de Investigación en Familia, 2025)
In recent years, the Boletín Semillero de Investigación en Familia has experienced remarkable growth in visibility and reach. Its evolution is reflected in the sustained increase in visits and downloads on the platform, the establishment of international collaborations, and the consolidation of a growing academic profile. The journal, founded in 2020 under the auspices of the Faculty of Health Sciences at the Universidad de los Llanos, has advanced in its indexing process and seeks to expand its presence in international databases. The active participation of authors and readers from the Orinoquía region, together with the institutional support of the Faculty of Health Sciences, has been key to its positioning. However, challenges remain: achieving recognition in global prestige indexes, promoting the internationalization of the editorial committee and contributing authors, and maintaining high-quality standards. This editorial describes the journal’s recent trajectory, highlighting its strengths and challenges, based on internal statistical data and literature on open access and scientific reach.
Keywords: Indexing; Open access; Global reach; Academic journals; Scientific journals